ANALISIS PERAN GURU DALAM MENINGKATKAN MINAT SISWA MA PLUS TARUNA TEKNIK AL-JABBAR MEDAN DALAM PEMBELAJARAN BAHASA ARAB - Salsabyila, Siti Nur; Muhammad Haical Eriyanto Marpaung; Sahkholid Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Arabic at Madrasah Aliyah Plus Taruna Teknik Al-Jabbar Medan holds a strategic role in supporting students' understanding of Islamic values and language skills. This research aims to identify and examine the role of teachers in enhancing students' interest and motivation in learning Arabic. The research employs a qualitative descriptive method, with data collected through observations and interviews. The findings reveal that although the Arabic curriculum has been designed in accordance with the standards of the Ministry of Religious Affairs, challenges persist in the implementation of learning activities, such as low student motivation and limited time. Teachers play a crucial role in overcoming these challenges through innovative and varied teaching methods, the use of technology, and personal approaches aligned with students' interests. A supportive classroom environment and interactive teaching methods are key to boosting students' motivation and interest in learning.This study is expected to provide positive encouragement for the development of Arabic education in madrasah aliyah.